Influenza Vaccine Effectiveness in Households With Children During the 2012-2013 Season: Assessments of Prior Vaccination and Serologic Susceptibility - Ohmit, Suzanne E.; Petrie, Joshua G.; Malosh, Ryan E.; Fry, Alicia M.; Thompson, Mark G.; Monto, Arnold S. (The Journal of infectious diseases, 2015)
Background. There are recognized needs to identify determinants of influenza vaccine effectiveness (VE), including the effect of repeated annual vaccination. Methods. We recruited 321 households with 1426 members, including 833 children, and followed them during the 2012-2013 influenza season; specimens were collected from subjects with reported acute respiratory illnesses. We estimated the effectiveness of documented influenza vaccination in preventing laboratory-confirmed influenza, using adjusted Cox proportional hazards models. Antibody titers in a subset of subjects were determined by a hemagglutination inhibition assay to determine the subjects' preseason susceptibility to influenza. Results. Influenza was identified in 76 (24%) households and 111 (8%) individuals. VE point estimates indicated significant protection in adults (48%; 95% confidence interval [CI], 1%-72%), similar protection in children aged 9-17 years (49%; 95% CI, -16% to 78%), but no evidence of effectiveness in children aged <9 years (-4%; 95% CI, -110% to 49%). Lower VE was observed in those vaccinated in both the current and prior seasons, compared with those vaccinated in the current season only; susceptibility titers against type A but not type B were consistent with this observation. Residual protection from vaccination in the prior season was indicated by both VE and sérologie results. Conclusions. Prior vaccination appears to modify VE by both residual protection and reduced vaccine response.